Drying characteristics of electro-osmosis dewatered sludge. Issue 23 (1st December 2016) - Ma, Degang; Qian, Jingjing; Zhu, Hongmin; Zhai, Jun
ABSTRACT: Electro-osmotic dewatering (EDW) is one of the effective deeply dewatering technologies that is suitable for treating sludge with 55–80% of moisture content. Regarding EDW as the pre-treatment process of drying or incinerating, this article investigated the drying characteristics of electro-osmosis-dewatered sludge, including shear stress test, drying curves analysis, model analysis, and energy balance calculation. After EDW pre-treatment, sludge adhesion was reduced. The sludge drying rate was higher compared to the non-pre-treated sludge, especially under high temperatures (80–120°C). In addition, it is better to place the sludge cake with cathode surface facing upward for improving the drying rate. An adjusted model based on the Logarithmic model could better describe the EDW sludge drying process. Using the energy balance calculation, EDW can save the energy consumed in the process of sludge incineration and electricity generation and enable the system to run without extra energy input.